Particulate matter aggravates Alzheimer's disease by activating the NLRP3 inflammasome to release ASC specks. Issue 8 (14th July 2021) - Zheng, Runxiao; Zhang, Jing; Han, Xiaoqing; Wu, Yunyun; Yan, Jiao; Song, Panpan; Wang, Yanjing; Wu, Xiaqing; Zhang, Haiyuan
Abstract : PM2.5 activated the NLRP3 inflammasome to release ASC specks and interact with the Aβ monomer to induce Aβ aggregation, further inducing AD. Abstract : Growing evidence has revealed the potential risk of ambient particulate matter (PM) causing chronic toxic influence on the nervous system of humans; however, it remains unclear whether PM could exacerbate Alzheimer's disease (AD). PM2.5 possesses complex physicochemical properties and can trigger various chronic toxicological responses, which potentially correlate with the aggravation of AD pathogenesis. Herein, PM2.5 was found to be able to activate the NLRP3 inflammasome in microglial cells (BV2) through multiple approaches, leading to the release of ASC specks, which could accelerate Aβ aggregation and promote neuronal apoptosis. After intranasal exposure to PM2.5 for 13 weeks, the hippocampus region of APP/PS1 mice showed the ASC speck release and Aβ aggregation. In addition, the high concentration of PM2.5 could cause a marked neuronal hypocellularity and spatial memory ability deficits in APP/PS1 mice. These results suggest the intense correlation between PM2.5 and AD based on the activation of the NLRP3 inflammasome.